Chemsex among men who have sex with men during the Mpox health crisis in Brazil - Santos, Guilherme Reis de Santana (2024)
Funding Information: This work was supported by Coordena\u00E7\u00E3o de Aperfei\u00E7oamento de Pessoal de N\u00EDvel Superior 001\u20102023 and Funda\u00E7\u00E3o Ci\u00EAncia e Tecnologia, IP national support UIDP/04923/2020. Publisher Copyright: © 2024 The Authors. Public Health Nursing published by Wiley Periodicals LLC.